2010
DOI: 10.1016/j.jmb.2010.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Trypanosomal Histidyl-tRNA Synthetase Illuminate Differences between Eukaryotic and Prokaryotic Homologs

Abstract: Crystal structures of histidyl-tRNA synthetase from the eukaryotic parasites Trypanosoma brucei and Trypanosoma cruzi provide a first structural view of a eukaryotic form of this enzyme, and reveal differences from bacterial homologs. Histidyl-tRNA synthetases in general contain an extra domain inserted between conserved motifs 2 and 3 of the Class II aminoacyl-tRNA synthetase catalytic core. The current structures show that the three dimensional topology of this domain is very different in bacterial and archa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Several groups have also reported the identification of MetRS, IleRS, and LeuRS inhibitors with antitrypanosome activity (30)(31)(32)(33)(34)(35). Crystal structures have been solved for many of the aaRSs across several species (15), including the structures of HisRS (36) and TrpRS (37) from T. brucei, which will aid in understanding how to target these enzymes for HAT drug discovery. Finally, we recently showed that a number of aaRSs from T. brucei associate into a MARS complex (21).…”
mentioning
confidence: 99%
“…Several groups have also reported the identification of MetRS, IleRS, and LeuRS inhibitors with antitrypanosome activity (30)(31)(32)(33)(34)(35). Crystal structures have been solved for many of the aaRSs across several species (15), including the structures of HisRS (36) and TrpRS (37) from T. brucei, which will aid in understanding how to target these enzymes for HAT drug discovery. Finally, we recently showed that a number of aaRSs from T. brucei associate into a MARS complex (21).…”
mentioning
confidence: 99%
“…Histidyl-tRNA synthetase (HisRS) 3HRI [140] 3HRK, 3LC0 [140] Histo-aspartic protease (HAP) 3FNS, 3FNT, 3FNU [141] β-Hydroxyacyl-acyl carrier protein Dehydratase (FabZ) 3AZ8, 3AZ9, 3AZA, 3AZB [142] (E)-4-hydroxy-3-methyl-but-2-enyl-diphosphate reductase (LytB)…”
Section: Brucei T Cruzimentioning
confidence: 99%
“…Furthermore, in many eukaryotes, the HisRS contains one or more copies of a short, N-terminal domain named WHEP. The WHEP domains are present in several non-homologous aaRSs and mediate different biological activities not related to aminoacyl-tRNA synthesis (Freist et al 1999 ;Merritt et al 2010 ).…”
Section: Histidyl-trna Synthetasementioning
confidence: 99%
“…The sequence identity between both trypanosomal HisRS and previously studied bacterial homologs is on the order of 25 % in the catalytic domain and lower elsewhere. When compared to both human HisRS sequences (HARS1 and HARS2), trypanosomal enzymes present an identity of less than 30 % (Merritt et al 2010 ).…”
Section: Histidyl-trna Synthetasementioning
confidence: 99%
See 1 more Smart Citation